Institusi Pendidikan Islam Indonesia Era Milenial - Budi Mansur (Sekolah Tinggi Agama Islam al-Amin, Gersik, Kediri, Lombok Barat, NTB, 2021)
Humans live in the millennial era. The continuation of this global era has created new challenges that must be utilized as well as possible, so that these challenges bring blessings to everyone who does it. Millennials, who look like both sides of the same coin, have both positive and negative impacts. Millennials are inspired not only by capitalism but also by pragmatism which has practically influenced education in Indonesia. The role of education becomes practically unknown and far from the needs of society.To face this era, what should Islamic education do as a sub-system of national education? Islamic schools (madrasas) as a sub-system of Islamic education in Indonesia, have very strong experience to face challenges in the last Dutch colonialism era.The fact that the madrasa has not only autonomy but also intellectual resources has proven that it can meet the needs of Islamic society. Millennials as a process of cultural transformation affect the world, especially the practice of education in Indonesia. Everyone using science and technology can easily access global culture. A value-free global culture must be faced with the transformation of values ​​that Islamic scholars have changed in pesantren (Islamic boarding schools) and Islamic schools (madrasas).In other words, both pesantren and madrasas should not be trapped in ideological capitalism and can serve everyone. That is because the paradigm of Islamic Education is different from both capitalism and pragmatism.